Nonlinearity compensation for two-zone energy-shaping control systems of DC drive - Biletskyi, Roman; Biletskyi, Yurii (Видавництво Львівської політехніки, 2017)
DC machines are the keystone of world industry. Working in second zone they behave as nonlinear objects. One of the newest methods of control system design for such machine as a part of electromechanical systems are energybased approaches. Energy-shaping control systems based on simplified model don’t work in second zone and the use of accurate model leads to many complications. This article contains description and comparative researches of proposed nonlinearity compensators that allows to use simplified control system. It was shown that reference signal corrector provides highly effective control, but there are still many possibilities to increase energy-shaping system’s efficiency
Keywords: DC motor; nonlinear control; two-zone control; energy-based approach; energy-shaping control system; portcontrolled Hamiltonian system